Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

In an AP , if Mth term is n and Nth term is m ,where M is not equal to N, find the Pth term..

In an AP , if Mth term is n and Nth term is m ,where M is not equal to N, find the Pth term..

Grade:11

2 Answers

Adhiraj Mandal
32 Points
8 years ago

Dear Vishal,

The m-th term is a+(m-1)d=n and the n-th term is a+(n-1)d=m

Therefore,a+md-d=n and a+nd-d=m

Subtracting the second result from the first result we get

a+md-d-a-nd+d=n-m

this implies,(m-n) d=(n-m)

therefore,d=(-1)

Therefore the p-th term is a+(p-1)d=a+(p-1)(-1)=a-p+1

I Hope I have come to your help.

With Regards,ADHIRAJ

Aâkäsh Kùmãr Pândéý
44 Points
4 years ago
We have am= a+(m-1)d=n........(1) and an= a+(n-1)d=m........(2)Solving (1) & (2), we get (m-n)d= n-m, or d= -1,And a=n+m-1Therefore ap = a+(p-1)d =n+m-1+(p-1) (-1)= n+m-pHence, the pth term is n+m-p.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free